2014
DOI: 10.1109/tbme.2014.2311856
|View full text |Cite
|
Sign up to set email alerts
|

Which Spring is the Best? Comparison of Methods for Virtual Stenting

Abstract: This paper presents a methodology for modeling the deployment of implantable devices used in minimally invasive vascular interventions. Motivated by the clinical need to perform preinterventional rehearsals of a stent deployment, we have developed methods enabling virtual device placement inside arteries, under the constraint of real-time application. This requirement of rapid execution narrowed down the search for a suitable method to the concept of a dynamic mesh. Inspired by the idea of a mesh of springs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…It is difficult for clinicians to monitor patient’s intra-aneurismal pressure change before and after stenting, so the change of pressure was rarely discussed in the previous studies. Shobayasi[26] studied the impact of virtual Neuroform stent implantation in a case of a large ICA-OphA aneurysm and found that the flow velocity within the aneurysm was reduced by 14%, but the pressure was only reduced by 4mmHg, which was much larger than our result. Makoto[13] virtually implanted an Enterprise stent into an ICA-OphA aneurysm, and reported that mean pressure at the inflow zone of aneurysm dropped from 43.56Pa to 28.23Pa and mean pressure at the dome of aneurysm dropped from 8.06Pa to 1.7Pa, similar to our findings.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…It is difficult for clinicians to monitor patient’s intra-aneurismal pressure change before and after stenting, so the change of pressure was rarely discussed in the previous studies. Shobayasi[26] studied the impact of virtual Neuroform stent implantation in a case of a large ICA-OphA aneurysm and found that the flow velocity within the aneurysm was reduced by 14%, but the pressure was only reduced by 4mmHg, which was much larger than our result. Makoto[13] virtually implanted an Enterprise stent into an ICA-OphA aneurysm, and reported that mean pressure at the inflow zone of aneurysm dropped from 43.56Pa to 28.23Pa and mean pressure at the dome of aneurysm dropped from 8.06Pa to 1.7Pa, similar to our findings.…”
Section: Discussioncontrasting
confidence: 67%
“…"Fast Virtual Stenting (FVS)" uses only deformable meshes, simple geometrical constraints, and neglects material properties. It greatly reduces the time of stent deployment, but with poor accuracy, especially for complex tortuous blood vessels [16, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently a number of virtual intervention tools are available (Ma, et al 2012, Appanaboyina, et al 2009, Larrabide, et al 2012, Spranger, et al 2014, Cebral et al 2005, Damiano et al 2015) but none has been adopted by the clinicians, largely because these tools lack the computational efficiency and an easy streamlined structure to be translated to the clinical settings, or are not accurate enough to represent the actual deployed stents in patient-specific aneurysms. The current study addresses this problem by developing a virtual stenting tool for neurovascular stents and flow diverters aimed at potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Larrabide et al overcame this problem by expanding a simplex mesh structure instead of a geometrical surface, and incorporating simplified forces among the stent struts and between the stent struts and the parent vessel in their modeling (Larrabide et al 2012). However, concerns have been raised on the lack of accuracy of this method in complex tortuous vessel geometries (Spranger et al 2014). In these cases the differences due to the expansion of a simplex mesh instead of the actual stent struts are magnified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have recently proposed 17 a virtual stent-deployment method able to predict the local properties of braided stents (wire location, angles, porosities) and implantation parameters (stent length, landing zone) with minimal computational cost. Contrary to other methods that involve either cumbersome finite element analysis [18][19][20][21] or complex phenomenologic constraints 13,20,[22][23][24][25][26] to simulate the stent dynamics, the proposed model is based on a minimal number of geometric assumptions (ie, a constant interwire distance and tubular stent envelope), which were validated in vitro and in vivo for the Pipeline Embolization Device (PED; Covidien, Irvine, California).…”
mentioning
confidence: 99%